Effects of Intensive Late-Season Sheep Grazing Following Early-Season Steer Grazing on Population Dynamics of Sericea Lespedeza in the Kansas Flint Hills - J. Lemmon; W. H. Fick; J. A. Alexander; G. W. Preedy; C. A. Gurule; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2016)
Sericea lespedeza (Lespedeza cuneata; SL) is a high-tannin, invasive forb in the Tallgrass Prairie ecosystem. In Kansas, sericea lespedeza infests 980 square miles of pasture, primarily in the Flint Hills region. Sericea lespedeza infestations reduce native grass production by up to 92% through a combination of aggressive growth, prolific reproduction, canopy dominance, and chemical inhibition (allelopathy). Herbicides retard the spread of sericea lespedeza, but application is laborious and expensive; moreover, herbicides are lethal to ecologically-important, non-target plant species. Increased grazing pressure on sericea lespedeza by domestic herbivores may slow its spread and facilitate some measure of biological control. Unfortunately, mature plants contain high levels of condensed tannins, which are a strong deterrent to grazing by beef cattle. Small ruminants have greater tolerance for condensed tannins than beef cattle. Sheep, in particular, appear less susceptible to certain plant toxins than beef cattle and may be useful to selectively pressure noxious weeds like sericea lespedeza. The predominant grazing management practice in the Flint Hills region of Kansas involves annual spring burning followed by intensive grazing with yearling beef cattle from April to August. During seasonal grazing, 40 to 60% of annual graminoid production is removed and pastures remain idle for the remainder of the year. Under this prevailing management practice, invasion by sericea lespedeza into the Tallgrass Prairie biome has steadily increased. Sericea lespedeza flowers and produces seed in late summer from August to September. The absence of grazing pressure during this interval strongly promotes seed production, seed distribution, and continued invasion of the Flint Hills ecoregion by this noxious weed. Therefore, the objective of our study was to evaluate effects of late-season sheep grazing following locally-conventional steer grazing on vigor and reproductive capabilities of sericea lespedeza.
Keywords: sericea; sheep; defoliation